1993
DOI: 10.1042/bj2940271
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast-specific factor 2: cloning of a putative bone adhesion protein with homology with the insect protein fasciclin I

Abstract: A cDNA library prepared from the mouse osteoblastic cell line MC3T3-E1 was screened for the presence of specifically expressed genes by employing a combined subtraction hybridization/differential screening approach. A cDNA was identified and sequenced which encodes a protein designated osteoblast-specific factor 2 (OSF-2) comprising 811 amino acids. OSF-2 has a typical signal sequence, followed by a cysteine-rich domain, a fourfold repeated domain and a C-terminal domain. The protein lacks a typical transmembr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
566
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 595 publications
(602 citation statements)
references
References 35 publications
14
566
0
2
Order By: Relevance
“…Periostin has a typical signal sequence, followed by a cysteine-rich domain, four repeated and conserved domains and a C-terminal hydrophilic domain (Takeshita et al, 1993;Horiuchi et al, 1999). A similar structure was reported for fasciclin I, a cell adhesion molecule involved in the development of the central nervous system of insects (Zinn et al, 1988), and for the big-h3 molecule, a secreted protein induced by TGF-b1 which promotes the attachment and spreading of fibroblasts (Skonier et al, 1992;LeBaron et al, 1995).…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Periostin has a typical signal sequence, followed by a cysteine-rich domain, four repeated and conserved domains and a C-terminal hydrophilic domain (Takeshita et al, 1993;Horiuchi et al, 1999). A similar structure was reported for fasciclin I, a cell adhesion molecule involved in the development of the central nervous system of insects (Zinn et al, 1988), and for the big-h3 molecule, a secreted protein induced by TGF-b1 which promotes the attachment and spreading of fibroblasts (Skonier et al, 1992;LeBaron et al, 1995).…”
Section: Introductionmentioning
confidence: 66%
“…Periostin is a secreted 90 kDa protein originally identified as an osteoblast-specific factor preferentially expressed in the periosteum in bone tissues (Takeshita et al, 1993;Horiuchi et al, 1999). Periostin has a typical signal sequence, followed by a cysteine-rich domain, four repeated and conserved domains and a C-terminal hydrophilic domain (Takeshita et al, 1993;Horiuchi et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…OSF2 is expressed in osteoblasts and lung tissue (Takeshita et al, 1993) and has shown altered expression in a number of human tumors (Gillan et al, 2002;Yoshioka et al, 2002). OSF2 has been suggested to have a tumor suppressor function in human oncogenesis (Yoshioka et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Periostin was originally identified as an 811-amino acid protein secreted by murine osteoblasts, which had structural homology to the insect axonal guidance protein fasciclin-1 (Takeshita et al 1993). Originally termed osteoblast specific factor-2 (OSF-2), it was renamed periostin due localized expression in the periosteum and the periodontal ligament (Kruzynska-Frejtag et al 2004).…”
Section: Periostin: a Novel Matricellular Proteinmentioning
confidence: 99%